2018
DOI: 10.3389/fncel.2018.00091
|View full text |Cite
|
Sign up to set email alerts
|

miR-103 Promotes Neurite Outgrowth and Suppresses Cells Apoptosis by Targeting Prostaglandin-Endoperoxide Synthase 2 in Cellular Models of Alzheimer’s Disease

Abstract: miR-103 has been reported to be decreased in brain of transgenic mouse model of Alzheimer’s disease (AD) and in cerebrospinal fluid (CSF) of AD patients, while the detailed mechanism of its effect on AD is obscure, thus this study aimed to investigate the effect of miR-103 expression on neurite outgrowth and cells apoptosis as well as its targets in cellular models of AD. Blank mimic (NC1-mimic), miR-103 mimic, blank inhibitor (NC2-mimic) and miR-103 inhibitor plasmids were transferred into PC12 cellular AD mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Rat pheochromocytoma cell line PC12 and human embryonic kidney cells 293T cell line were purchased from Cell Resource Center of Shanghai Institute of Life Sciences, Chinese Academy of Sciences (Shanghai, China). Primary cerebral cortex neurons from rat embryo were acquired according to the methods as described in our previous study [13].…”
Section: Cells Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat pheochromocytoma cell line PC12 and human embryonic kidney cells 293T cell line were purchased from Cell Resource Center of Shanghai Institute of Life Sciences, Chinese Academy of Sciences (Shanghai, China). Primary cerebral cortex neurons from rat embryo were acquired according to the methods as described in our previous study [13].…”
Section: Cells Sourcesmentioning
confidence: 99%
“…In our previous study, we observed that miR-103 promoted neurite outgrowth and suppress cell apoptosis by targeting prostaglandin-endoperoxide synthase 2 (PTGS2) in two cellular models of AD (PC12 cellular AD model and cellular AD model of rat cerebral cortex neurons), however, the upstream regulator of miR-103 in AD is still unclear [13]. According to the data retrieved from miRanda Database (http://www.microrna.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al reported that miR-103 enhances the proliferation of gastric cancer cells by targeting klf4 [ 39 ]. It was also found that miR-103 promotes neurite outgrowth and reduces cell apoptosis by targeting prostaglandin-endoperoxide synthase 2 (PTGS2) in cellular models of Alzheimer’s disease [ 40 ]. Recently, a few studies reported that miR-195 and miR-15b play roles that contribute to cell proliferation as oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…As for miR‐103 and miR‐107, a study conducted in cellular model of AD exhibited that miR‐103 promotes neurite outgrowth and suppresses cell apoptosis by targeting PTGS2 . And miR‐107 upregulation is shown to facilitate cell survival, reduce lactate dehydrogenase leakage, and inhibit apoptosis and Aβ production in AD .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that miR‐103 and miR‐107, belonging to the same family and only differ at one nucleotide residue near the 3′ end, are differentially expressed in CSF of AD patients and have evolutionary conserved binding sites for AD‐related gene, a disintegrin and metalloproteinase 10 (ADAM10) . Moreover, miR‐103 is previously shown to promote neurite outgrowth and suppresses neuron apoptosis by targeting prostaglandin‐endoperoxide synthase 2 (PTGS2) in AD . Nonetheless, the predictive value of circulating miR‐103 and miR‐107 for AD susceptibility and progression is still unknown.…”
Section: Introductionmentioning
confidence: 99%